2017
DOI: 10.1186/s12957-017-1211-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key lncRNAs in colorectal cancer progression based on associated protein–protein interaction analysis

Abstract: BackgroundColorectal cancer (CRC) was one of the most commonly diagnosed malignancies. The molecular mechanisms involved in the progression of CRC remain unclear. Accumulating evidences showed that long noncoding RNAs (lncRNAs) played key roles in tumorigenesis, cancer progression, and metastasis. Therefore, we aimed to explore the roles of lncRNAs in the progression of CRC.MethodsIn this study, we aimed to identify differentially expressed lncRNAs and messenger RNAs (mRNAs) in CRC by analyzing a cohort of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Accumulating evidence has demonstrated that lncRNAs exert complex effects in cancer progression (27,28). Abnormally expressed lncRNAs have been recognized to exert oncogenic properties in NSCLC, for instance, upregulated lncRNA maternally expressed 3 was observed to inhibit NSCLC cell proliferation and induce apoptosis by affecting p53 expression (29).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that lncRNAs exert complex effects in cancer progression (27,28). Abnormally expressed lncRNAs have been recognized to exert oncogenic properties in NSCLC, for instance, upregulated lncRNA maternally expressed 3 was observed to inhibit NSCLC cell proliferation and induce apoptosis by affecting p53 expression (29).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Some lncRNAs have been reported to be differentially expressed in colorectal cancer tissues and cells, but their functions have been verified. 14 For example, lncRNA DLEU1 promoted CRC cell progression through regulating KPNA3. 15 Moreover, lncRNA CRNDE induced cell proliferation and chemoresistance in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PGM5-AS1 (NCBI, Gene, NR_015423) has been reported to regulate the miR-466/PTEN axis to exert tumor-suppressive effects in esophageal squamous cancer [22]; furthermore, abnormally low expression of PGM5-AS1 is related to the poor prognosis of renal clear cell carcinoma [23]. Zhu et al [24]downloaded the original microarray data set (GSE64857) containing analysis data of gene expression of patients suffering recurrent and non-recurrent CRC, and performed bioinformatics analysis to show that PGM5-AS1 was highly co-expressed with differentially expressed mRNAs. However, no further studies of the role and underlying molecular mechanism of PGM5-AS1 in colon cancer has been carried out.…”
Section: Resultsmentioning
confidence: 99%